TGR5 Activation Ameliorates Mitochondrial Homeostasis via Regulating the PKCδ/Drp1-HK2 Signaling in Diabetic Retinopathy - Zhang, Meng-Yuan; Zhu, Lingpeng; Zheng, Xinhua; Xie, Tian-Hua; Wang, Wenjuan; Zou, Jian; Li, Yan; Li, Hong-Ying; Cai, Jiping; Gu, Shun; Yao, Yong; Wei, Ting-Ting (Frontiers in Cell and Developmental Biology, 2022)
Background: Diabetic retinopathy (DR) is one of the most important microvascular diseases of diabetes. Our previous research demonstrated that bile acid G-protein-coupled membrane receptor (TGR5), a novel cell membrane receptor of bile acid, ameliorates the vascular endothelial cell dysfunction in DR. However, the precise mechanism leading to this alteration remains unknown. Thus, the mechanism of TGR5 in the progress of DR should be urgently explored. Methods: In this study, we established high glucose (HG)-induced human retinal vascular endothelial cells (RMECs) and streptozotocin-induced DR rat in vitro and in vivo. The expression of TGR5 was interfered through the specific agonist or siRNA to study the effect of TGR5 on the function of endothelial cells in vitro. Western blot, immunofluorescence and fluorescent probes were used to explore how TGR5 regulated mitochondrial homeostasis and related molecular mechanism. The adeno-associated virus serotype 8-shTGR5 (AAV8-shTGR5) was performed to evaluate retinal dysfunction in vivo and further confirm the role of TGR5 in DR by HE staining, TUNEL staining, PAS staining and Evans Blue dye. Results: We found that TGR5 activation alleviated HG-induced endothelial cell apoptosis by improving mitochondrial homeostasis. Additionally, TGR5 signaling reduced mitochondrial fission by suppressing the Ca2+-PKCδ/Drp1 signaling and enhanced mitophagy through the upregulation of the PINK1/Parkin signaling pathway. Furthermore, our result indicated that Drp1 inhibited mitophagy by facilitating the hexokinase (HK) 2 separation from the mitochondria and HK2-PINK1/Parkin signaling. In vivo, intraretinal microvascular abnormalities, including retinal vascular leakage, acellular capillaries and apoptosis, were poor in AAV8-shTGR5-treated group under DR, but this effect was reversed by pretreatment with the mitochondrial fission inhibitor Mdivi-1 or autophagy agonist Rapamycin. Conclusions: Overall, our findings indicated that TGR5 inhibited mitochondrial fission and enhanced mitophagy in RMECs by regulating the PKCδ/Drp1-HK2 signaling pathway. These results revealed the molecular mechanisms underlying the protective effects of TGR5 and suggested that activation of TGR5 might be a potential therapeutic strategy for DR.